One‐year effectiveness and safety of vedolizumab therapy for inflammatory bowel disease: a prospective multicentre cohort study. Issue 3 (8th June 2017) - Amiot, A.; Serrero, M.; Peyrin‐Biroulet, L.; Filippi, J.; Pariente, B.; Roblin, X.; Buisson, A.; Stefanescu, C.; Trang‐Poisson, C.; Altwegg, R.; Marteau, P.; Vaysse, T.; et al.
Summary: Background: We recently showed that vedolizumab is effective in patients with Crohn's disease (CD) and ulcerative colitis (UC) with prior anti‐TNF failure in a multicentre compassionate early‐access programme before marketing authorisation was granted to vedolizumab. Aims: To assess effectiveness and safety of vedolizumab at week 54 in patients UC and CD. Methods: Between June and December 2014, 173 patients with Crohn's disease (CD) and 121 with ulcerative colitis (UC) were treated with vedolizumab induction therapy. Among those 294 patients, 272 completed the induction period and were evaluated at the week 14 visit (161 patients with CD and 111 with UC). Disease activity was assessed using the Harvey‐Bradshaw Index for CD and the partial Mayo Clinic score for UC. The primary outcome was steroid‐free clinical remission at week 54. Results: At week 54, steroid‐free clinical remission rates at week 54 were 27.2% and 40.5% in patients with CD and UC respectively. In addition, the sustained steroid‐free clinical remission (from week 14 to week 54) rates were 8.1% and 19.0% respectively. No deaths were observed. Severe adverse events occurred in 17 (7.2%) patients, including six (2.5%) leading to vedolizumab discontinuation. Conclusion: Vedolizumab is able to maintain steroid‐free clinical remission in up to one‐third of patients with UC and CD at week 54 with a reasonable safety profile. A significant number of patients experienced loss of response during the first year of treatment, particularly in patients with CD. Abstract : Linked Content This article is linked to Speight and Mansfield papers. To view this article visithttps://doi.org/10.1111/apt.14215 .